"Drop-on-textile" patternable aqueous PEDOT composite ink providing highly stretchable and wash-resistant electrodes for electronic textiles. (August 2018) - Kye, Min Jung; Cho, Jinhan; Yu, Jae Chul; Chang, Young-Wook; Han, Jihye; Lee, Eunji; Lim, Ho Sun; Lim, Jung Ah
Abstract: We demonstrate a direct-write patternable water-based poly (3, 4-ethylenedioxythiophene): poly (styrene sulfonate) (PEDOT:PSS) composite ink which is capable of providing highly stretchable and washing-resistant electrodes on a fabric substrate for electronic textile applications. An aqueous composite ink consisting of PEDOT:PSS, graphene oxide nanosheets and anionic polyurethane does readily not permeated into hygroscopic fabric, which facilitate direct drawing of fine PEDOT electrode on the fabric without undesired blur effect. This limited permeation of aqueous PEDOT composite ink on the hygroscopic fabric is mainly originated from the intermolecular interactions of anionic polyurethane including hydrogen bonding with water molecules, and charge balancing interactions with PEDOT chains. Furthermore, addition of the graphene oxide nanosheets contributes to enhance the electrical conductivity of the composite by improving crystallization of PEDOT molecules. The PEDOT composite film shows unique structure of the PEDOT nanofibril network embedded by the polyurethane matrix, which resulted in an enough electrical pathway for charge carriers even though only 2.9 wt% of PEDOT:PSS existed in the composite film. The PEDOT composite film exhibited electrical conductivity of 4.6 S/cm, extremely high stretchability of 375% rupture strain, and high durability for repeated washing process with strong bleaching agent. Light emitting diode incorporated on the stretchable spandex with interconnects of the PEDOT composite pattern showed that LED light intensity was almost maintained even with stretching of PEDOT interconnects to 290%. Graphical abstract: Highlights: A direct patternable aqueous PEDOT:PSS composite ink providing stretchable and wash-resistant electrodes was demonstrated. Addition of graphene oxide and anionic polyurethane to PEDOT:PSS solution facilitate direct drawing of fine PEDOT electrode on the fabric. Limited permeation of aqueous PEDOT composite ink is originated from the intermolecular interactions of additives with PEDOT molecules. The PEDOT composite film shows unique structure of the PEDOT nanofibril network embedded by the polyurethane matrix. The PEDOT composite electrodes exhibited good electrical properties and high durability for repeated washing process.